Hyers-Ulam-Rassias Stability of the \(C^*\)-ternary Bi-homomorphisms and \(C^*\)-ternary Bi-derivations in \(C^*\)-ternary Algebras - Kaskasem, Prondanai; Klin-eam, Chakkrid (Communications in Mathematics and Applications, 2019)
In this  paper, we prove Hyers-Ulam-Rassias stability of \(C^*\)-ternary bi-homomorphisms and \(C^*\)-ternary bi-derivations in \(C^*\)-ternary algebras by using alternative fixed point theorem.
Keywords: Hyers-Ulam-Rassias stability; \(C^*\)-ternary bi-homomorphisms; \(C^*\)-ternary bi-derivations; \(C^*\)-ternary algebras